Programming Robots in Kindergarten - Nikolić, Sanja; Hilčenko, Slavoljub (The University of Rzeszów Publishing House, 2023)
Children at an early age easily acquire new technical and technological knowledge, and their abilities and skills surpass all expectations. Nowadays, children are already familiar with and interested in new technologies from a very young age, as it is an integral part of everyday life and has great potential for future development. In light of this, programming robots in kindergarten emerges as a very relevant and popular topic, which is precisely the subject of this paper.
Keywords: robotics; preschool age; robot programming; kindergarten